2004
DOI: 10.1037/0893-3200.18.1.250
|View full text |Cite
|
Sign up to set email alerts
|

Coming Home Upset: Gender, Marital Satisfaction, and the Daily Spillover of Workday Experience Into Couple Interactions.

Abstract: , R. T. (2004). Coming home upset: Gender, marital satisfaction and the daily spillover of workday experience into marriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
202
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(224 citation statements)
references
References 40 publications
18
202
1
3
Order By: Relevance
“…Moreover, daily diary research has demonstrated that tensions between partners are more likely to occur on days when spouses experienced tension at work (Bolger, DeLongis, Kessler, & Wethington, 1989). Specifically, negatively arousing workdays have been linked with more withdrawn behavior in the home (Repetti, 1989;Schulz, Cowan, Cowan, & Brennan, 2004). Conditions of high stress also appear to diminish spouses' propensity for engaging in forgiving responses to a partner's transgressions (Neff & Karney, 2004;Neff & Karney, 2009).…”
Section: Stress and Marital Quality: Spillover Effectsmentioning
confidence: 99%
“…Moreover, daily diary research has demonstrated that tensions between partners are more likely to occur on days when spouses experienced tension at work (Bolger, DeLongis, Kessler, & Wethington, 1989). Specifically, negatively arousing workdays have been linked with more withdrawn behavior in the home (Repetti, 1989;Schulz, Cowan, Cowan, & Brennan, 2004). Conditions of high stress also appear to diminish spouses' propensity for engaging in forgiving responses to a partner's transgressions (Neff & Karney, 2004;Neff & Karney, 2009).…”
Section: Stress and Marital Quality: Spillover Effectsmentioning
confidence: 99%
“…Within these studies on minor stress, several studies report a spillover of external stress (e.g., from work) on marital communication and quality (e.g., Bodenmann, 2000;Bodenmann et al, 2006;Bodenmann et al, 2007;Bolger et al, 1989;Repetti, 1989, Schulz, Cowan, Cowan, & Brennan, 2004. Although most of these studies were cross-sectional, some used multi-level analyses and addressed mediation processes between external stress, internal stress, and relationship quality (e.g., Bodenmann et al, 2007).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Wood, 1997; Schulz et al, 2004;Story & Repetti 2006), suggesting that more negatively arousing workdays were linked with negative marital behavior and emotions.…”
Section: Stress and Relationships 21mentioning
confidence: 99%
See 2 more Smart Citations